Environmental and Pro-Social Norms: Evidence from 30 Countries - Benno Torgler; Bruno S. Frey; Clevo Wilson (Center for Research in Economics, Management and the Arts (CREMA), 2007)
The paper investigates the relationship between pro-social norms and its implications for improved environmental outcomes, an area which has been neglected in the environmental economics literature. We provide empirical evidence, demonstrating a strong link between perceived environmental cooperation (reduced public littering) and increased voluntary environmental morale, using European Values Survey (EVS) data for 30 Western and Eastern European countries. The robust results suggest that environmental morale and perceived environmental cooperation, as well as identifying the factors that strengthen these relationships, potentially bring about better environmental outcomes.
Keywords: H26; H73; D64; 330; environmental preferences; environmental morale; conditional cooperation; pro-social behavior